Hydrothermally altered landslide deposits at Askja, Iceland - field data - Pouria Marzban; Stefan Bredemeyer; Thomas R. Walter; Friederike Kaestner; Daniel Mueller; Sabine Chabrillat (Zenodo, 2023)
Weanalyze the proximal deposits of the July 21, 2014 landslide at Askja (Iceland), by combining high-resolution imagery from Unoccupied Aircraft Systems (UAS) and in-situ hyperspectral field data.Results underline that the northern part of the landslide source region is a hydrothermally altered material class, which bifurcates halfway downslope and then extends to the lake. Here we provide the field data, such as the drone derived orthomosaic and digital elevation model (DEM), as well as hyperspectral field data. For locations of the data and measurements made we refer to the publication Pouria Marzban,Stefan Bredemeyer, Thomas R. Walter, Friederike Kaestner,Daniel Mueller and Sabine Chabrillat (2023)Hydrothermally altered landslide deposits at Askja, Iceland, identified by high resolution satellite and UAS imagery, spectral classification and hyperspectral field data.Frontiers in Earth ScienceVolcanology.Manuscript ID: 1083043 To preview or open the files: DEM - open in QGis or ArcMap or similar Orthomosaic - open in QGis or ArcMap or similar Point cloud - open in Metashape or CloudCompare or similar Hyperspectral - open in ENVI or similar